2013
DOI: 10.1080/0269249x.2013.851118
|View full text |Cite
|
Sign up to set email alerts
|

Diatom-based reconstruction of Middle to Late Holocene paleoenvironments in Lake Lonkoy, southern Pampas, Argentina

Abstract: Diatoms recovered from shallow Lake Lonkoy sediment core in southern Pampas, Argentina, were studied in order to assess past environmental conditions. A total of 47 samples were selected from a 1.42-m long core that spans the last 4840 cal. years. Diatoms were extracted by chemical cleaning and studied under light and scanning electron microscopy. A total of 89 diatom taxa were recorded, including 36 taxa that reached > 2% relative abundance and were used in statistical analyses. A cluster analysis allowed fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 49 publications
2
12
0
5
Order By: Relevance
“…This tidal inlet was characterized by deposits of estuarine mollusks such as Tagelus plebeius and H. australis, indicating a direct marine influence in that area. Our findings of H. australis in LK and SL suggest that this marine influence would have reached sites located even more distant, either directly or indirectly (as suggested by Hassan 2013).…”
Section: Evolution Of Molluscan Assemblagesmentioning
confidence: 71%
See 2 more Smart Citations
“…This tidal inlet was characterized by deposits of estuarine mollusks such as Tagelus plebeius and H. australis, indicating a direct marine influence in that area. Our findings of H. australis in LK and SL suggest that this marine influence would have reached sites located even more distant, either directly or indirectly (as suggested by Hassan 2013).…”
Section: Evolution Of Molluscan Assemblagesmentioning
confidence: 71%
“…The LK core was recovered with a 5-cm-diameter modified Livingston corer, in April 2009. The sedimentary section, which is 142 cm long, has been previously analyzed for pollen, NPPs, macrofossil remains (Stutz et al 2012), and diatoms (Hassan 2013), and it was divided into three lithological units (Table 1). Six AMS 14 C dates (from 4842 to 670 cal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Root penetration was evident in many short cores taken from Lake Nahuel Rucá (Cristini and De Francesco 2012). These Pampean lakes increased their nutrient levels during the late Holocene (Stutz et al 2012;Hassan 2013) and, consequently, their biological activity. At ca.…”
Section: Mollusk Preservationmentioning
confidence: 97%
“…Previous studies of these records indicated the occurrence of wide paleoenvironmental changes, particularly related to fluctuations in salinity, water depth, and nutrient status (Stutz et al 2010(Stutz et al , 2012De Francesco et al 2013;Hassan 2013). These environmental changes may have affected diatom and mollusk preservation in different ways.…”
Section: Introductionmentioning
confidence: 96%